Onyms as a Resource of Neologization in FB-Comments - Andreyeva , Tetyana (Current issues of Ukrainian linguistics: theory and practice, 2019)
The article discusses word-formation processes taking place in Internet communication (particularly, in Facebook comments), where onym denoting a public person is used in diverse modifications. It is alleged that Internet usage transformed people into participants of communication processes that have neither time nor spatial restrictions. The ability to use information technologies became not only the key of physical existence but also the assuarance of spiritual life for most people, as the World Wide Web is the main interactive environment where active mass communication takes place. The fact of conversion of social networks to sources of information is substantiated. It is determined that the language of Internet communication has a specific ability to adapt means of conversational speech to writing style specific to network communication. Communication in social networks, where there is an opportunity to speak practically uncensored, is characterized by looseness. Hence, limitless possibilities open up before its participants for the embodiment of their informative and expressional intensions. It is stated that Internet commenting allows its participants to demonstrate creative component of their personalities, represent their civil position, life views, evaluate any event etc. It is established that modern Ukrainian information space is characterized with a large number of onyms denoting public persons that are used as derivational materials in the processes of creating neologisms. To a large extent, this was facilitated by pre-election political technological moves, which consisted of creating a logo from the first syllable of the candidate's surname together with an exclamation mark – "Ze!" (Zelenskiy). The types of modifications of last name are found (reduction into one syllable, up to two syllables, cutting to the non-suffixed part), derivational methods and word making models are identified (morphological, semantic, analytical derivation). The processes associated with derivational acts have been clarified. The use of a language game involving multiple variations of the surname is stated. The range of perspectives of language of Internet communication research is outlined, which is constantly gaining momentum.
Keywords: Internet communication, comments, neologisms, prefix, social network, semantic derivatives, analytical derivation, language game.